2014
DOI: 10.1002/2013jd020937
|View full text |Cite
|
Sign up to set email alerts
|

Assimilating aerosol observations with a “hybrid” variational‐ensemble data assimilation system

Abstract: Total 550 nm aerosol optical depth, surface fine particulate matter (PM 2.5 ), and meteorological observations were assimilated with continuously cycling three-dimensional variational (3DVAR), ensemble square root Kalman filter (EnSRF), and hybrid variational-ensemble data assimilation systems. The hybrid system's background error covariances (BECs) were a blend of those in 3DVAR and produced by the cycling EnSRF system, and the 3DVAR, EnSRF, and hybrid systems differed almost exclusively by their BECs. New an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 104 publications
1
91
1
Order By: Relevance
“…The retrieved AOD can also be used for data assimilation with other satellite data (MODIS, Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) aerosol product, etc. ), ground-based measurements (AERONET, particulate matter (PM) observations, and meteorological observations) and model data (GOCART aerosol data) to further improve the air quality analyses and forecasts [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…The retrieved AOD can also be used for data assimilation with other satellite data (MODIS, Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) aerosol product, etc. ), ground-based measurements (AERONET, particulate matter (PM) observations, and meteorological observations) and model data (GOCART aerosol data) to further improve the air quality analyses and forecasts [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…The EnSRF algorithm was introduced by Whitaker and Hamill (2002) and its expansion to analysing aerosol ICs was described by Schwartz et al (2014). The traditional EnKF with perturbed observations (Evensen, 1994) introduces sampling errors by perturbing the observations.…”
Section: Ensemble Square Root Filter (Ensrf)mentioning
confidence: 99%
“…Peng et al: Improving PM 2.5 forecast over China et al, 2010a, b;Pagowski and Grell, 2012;Dai et al, 2014;Rubin et al, 2016;Ying et al, 2016;Yumimoto et al, 2016) and the hybrid variational-ensemble DA approach (Schwartz et al, 2014) have also been applied to aerosol predictions. All these studies have shown that DA is one of the most effective ways of improving aerosol forecasting through assimilating aerosol observations from multiple sources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of 6 h re-analyses for initialization led to notable improvements when both satellite and surface data were assimilated. More recently, Schwartz et al (2014) assimilated the same AOD and PM 2.5 surface concentration data using two additional methods: the EnSRF and a hybrid ensemble 3D-Var method. All three methods led to mostly improved forecasts, with the hybrid method showing the best performance and 3D-Var generally showing better performance than the EnSRF.…”
Section: Data Assimilation In Coupled Chemistry Meteorology Modelsmentioning
confidence: 99%